Emission characteristics of carboxylates in PM2.5 from incense burning with the effect of light on acetate - Kuo S. (2017)
© 2016 Elsevier Ltd. Incense burning produces potentially harmful particulate matter. In this study we investigated the emissions of PM 2.5 and gaseous acetic acid from four brands of traditional incense; Liao and Shang Lao Shan (SLS), sold in Taiwan, and Thai Yellow (Thai Y) and Thai Black (Thai B), sold in Thailand. Additionally, photochemical reactions of PM 2.5 carboxylates emitted from incense burning were studied via a simulated light experiment. The average PM 2.5 mass emission factor of each incense type was inversely correlated with the ash production of that incense. The Thailand incense carboxylate emissions were markedly higher than the Taiwan incense. Acetate accounted for 87.46% of total carboxylate emissions, with acetate emitted from the Thailand incense 1.26 times higher than from the Taiwan incense. Phthalate was detected in the PM 2.5 , indicating the presence of plasticizer. Concentrations of PM 2.5 acetate, formate, pyruvate, glutarate, succinate, fumarate and tartarate were reduced in simulated light (51.5%-97.1% of those under dark), indicating that these seven types of carboxylate are easily photodegradable. In contrast, malonate, maleate, oxalate and phthalate concentrations in light were 1.17-1.84 times higher than in darkness, indicating photochemical reactions contribute to the formation of these species. The formation of the low-molecular weight dicarboxylates oxalate and malonate was most noticeable. Acetic acid, highly irritating to the respiratory system and skin, was present at high levels for all four incense types, as shown by the gaseous acetic acid/PM 2.5 acetate ratios of 1.03-3.61. Burning incense indoors can generate high concentrations of PM 2.5 acetate that increases the risks of respiratory and contact irritation, particularly when burning the Thailand incense. Moreover, burning incense in poorly ventilated, dimly lit indoor areas (e.g., temples and homes) can markedly increase the risk of irritation because the gaseous acetic acid is not degraded as it would be in light.